Biomechanical & muscular differences in three jump conditions - Neugebauer, J. M.; Williams, K. R. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
As expected, CMJ and IPJ jump heights were greater than NCMJ jump heights, and these differences could be attributed to force and contractile potentiation at the start of the upward movement. While trends in the data showed CMJ jump heights to be slightly greater on average than IPJs, the differences were not statistically significant. Differences in pre-activation force levels of IPJs and CMJs were minimal and did not influence jump height. The non-significant results suggest that SSC contributions in the CMJs did not provide an overall increase in jump height compared to the IPJ condition, perhaps indicating that mechanisms such as contributions from elastic energy were not greater in the CMJ jump as might have been expected.